2021
DOI: 10.7196/samj.2021.v111i11b.16108
|View full text |Cite
|
Sign up to set email alerts
|

Profile of patients seen at Pietersburg and Mankweng breast cancer clinics in Limpopo

Abstract: Breast cancer is the most prevalent cancer and leading cause of death among women worldwide. [1] The average lifetime risk of breast cancer for a wom an in the USA has been estimated at 12.3% with about 41 400 deaths reported in 2018. [1] The global incidence increased from 1.7 million in 2005 to 2.4 million cases in 2015 [2] and in Africa is predicted to double by 2050. [3] Incidence rates are lower in low-and middle-income countries (LMICs) than in high-income countries; however, the rates are increasing ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Our patient was a 58-year-old female who presented at an advanced stage despite a growing rapidly breast mass. A previously published study by our institution by Bhuiyan et al [8] and other literature showed that breast cancer patients typically present late in this province. This patient is not different from others in terms of the timing of presentation to the hospital.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Our patient was a 58-year-old female who presented at an advanced stage despite a growing rapidly breast mass. A previously published study by our institution by Bhuiyan et al [8] and other literature showed that breast cancer patients typically present late in this province. This patient is not different from others in terms of the timing of presentation to the hospital.…”
Section: Discussionmentioning
confidence: 72%
“…This patient is not different from others in terms of the timing of presentation to the hospital. There are several factors contributing to the late presentation of breast cancer, which include lack of knowledge about breast cancer, symptoms of breast cancer, low levels of education, low socioeconomic status, traditional healer and spiritual beliefs and fear of hospitalisation [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…11 A similar trend was found among the women in Limpopo, South Africa. 12 No significant difference in the histological subtype of breast cancer was found between HIV-positive & HIV-negative patients. In our study, most (33) of HIV-positive patients presented with breast cancer in stage III (76.7%) and 8 patients (18.6%) with stage II.…”
Section: Discussionmentioning
confidence: 95%
“…11 A study done in Limpopo, in SA, showed that 38% of breast cancer patients were younger than 50 years. 12 Tygerberg Academic Hospital in SA reported a median age at presentation of 56 years for patients without HIV compared with 42 years for patients with HIV (P<001). 13 Edge et al found that patients with breast cancer in SSA usually appear to be at a younger age, irrespective of HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] This is followed by a two-year review of patients seen at the Pietersburg and Mankweng hospitals breast cancer clinic and a review of the profile of molecular subtyping of breast cancer and clinicopathological features. [4,5] Finally, the third part consists of a number of interesting surgical case reports, to provide an indication of the length and depth of surgical challenges in Limpopo Province. The first three case reports pertain to special cases of breast cancer.…”
mentioning
confidence: 99%